Sector and Country Balance of Trade Analysis Based on World Input-Output Database: Indonesian Economy - Muchdie Muchdie; Emaridial Ulza; Edi Setiawan (Universitas Muhammadiyah Ponorogo, 2018)
This paper analyses trade balance in Indonesian economy by using Indonesia input-output tables for the year 2000, 2005, 2010 and 2014. The results showed that, firstly, Indonesian export had been increased significantly during the year of study. Secondly, Indonesian import had also increased significantly during the year of study. Important sectors and countries’ trade partners of export and import had been indicated. Thirdly, trade balances in Indonesia economy were surpluses in all years of the study. Sectors and countries in which trade balances were deficits and surpluses had also been clearly indicated.